Assessment of color stability and translucency of various CAD/CAM ceramics of different compositions and Thicknesses: An in vitro study - Passent Ellakany; Nourhan M. Aly; Shahad T. Alameer; Turki Alshehri; Shaimaa M. Fouda (Elsevier, 2024)
Background: Translucency and optical characteristics significantly affect the aesthetics of ceramic restorations. The introduction of new virgilite crystals to novel ceramic advanced lithium disilicate through a matrix firing process enhances the material's strength and aesthetic quality according to the manufacturer. Materials and Methods: Four types of CAD/CAM ceramics; lithium disilicate (LD), leucite reinforced (LR), advanced lithium disilicate (ALD), and zirconia-reinforced lithium silicate (ZLS) exposed to different staining solutions (tea, cola, coffee, and distilled water). Each ceramic type had 120 specimens, divided into subgroups based on thickness (0.5 mm, 1 mm, and 1.5 mm). Color changes (ΔE00) and translucency parameters (TP00) were measured after thermocycling, and spectrophotometry was employed to evaluate ΔE00 and TP00 after 1, 7, and 30 days of exposure to the staining solutions. Results: ZLS exhibited the lowest color stability, while lithium LD and ALD displayed the highest. Thickness significantly affected color stability, with 0.5 mm thickness showing the least change. The duration of exposure also impacted color changes, with 30 days causing the most significant shift. LD demonstrated the highest translucency. Coffee and tea induced more pronounced reductions in translucency and color stability compared to the control group. Conclusions: Material structure, thickness, staining solution, and exposure duration significantly influenced the color stability and translucency of CAD/CAM ceramics, with LD and ALD demonstrating superior color stability and LD exhibiting the highest translucency.